Study of the Health Instructions Effect on Quality of Life and Psychological Problems among Children with Thalassemia (International Journal of Studies in Nursing, 2016)
Objective: The aim of this study was to evaluate the health instructions effect on quality of life and psychological problems among children with thalassemia. Design: Quasi-experimental design used in this study. Pre and post evaluation done to identify the effect of health instructions sessions which provided by the researchers for thalassemic children and their parents on children heath related quality of life and psychological problems using Pediatric quality of life inventory PedsQL